HUNGER FOR AUTHORITY IN RON HOWARD'S ANGELS AND DEMONS MOVIE (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - TIMUR, DIAN (2011)
This study investigates the hunger for authority that is reflected in Angels and Demons viewed from individual psychological approach. The aims of this study are to analyze the structural elements of the movie and to analyze the movie based on individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two types of data sources, namely primary and secondary data sources. The primary data sources and the object of the study is the movie itself, meanwhile the secondary one is any literature related to this study for example reading some other resources related to the movie. The writer collects the data from both primary and secondary data source in sort of document as evidence. The technique of analyzing data is descriptive. Based on the analysis, there are two conclusions. First, from the structural analysis it shows that each of the elements is interrelated to each other and forms unity. Second, from the individual psychological analysis, it shows that, religion needs science to defend the authority. Someone that has good knowledge, he or she can saves the religion.